Α-Lipoic Acid Targeting PDK1/NRF2 Axis Contributes to the Apoptosis Effect of Lung Cancer Cells. (4th June 2021) - Yue, Liduo; Ren, Yanbei; Yue, Qingxi; Ding, Zhou; Wang, Kai; Zheng, Tiansheng; Chen, Guojie; Chen, Xiangyun; Li, Ming; Fan, Lihong
Abstract : As an antioxidant, α -lipoic acid (LA) has attracted much attention to cancer research. However, the exact mechanism of LA in cancer progression control and prevention remains to be unclear. In this study, we demonstrated that α -lipoic acid has inhibitory effects on the proliferation, migration, and proapoptotic effects of non-small-cell lung cancer (NSCLC) cell lines A549 and PC9. LA-induced NSCLC cell apoptosis was mediated by elevated mitochondrial reactive oxygen species (ROS). Further study confirmed that it is by downregulating the expression of PDK1 (the PDH kinase), resulted in less phospho-PDH phenotype which could interact with Keap1, the negative controller of NRF2, directly leading to NRF2 decrease. Thus, by downregulating the NRF2 antioxidant system, LA plays a role in promoting apoptosis through the ROS signaling pathway. Moreover, LA could enhance other PDK inhibitors with the proapoptosis effect. In summary, our study shows that LA promotes apoptosis and exerts its antitumor activity against lung cancer by regulating mitochondrial energy metabolism enzyme-related antioxidative stress system. Administration of LA to the tumor-bearing animal model further supported the antitumor effect of LA. These findings provided new ideas for the clinical application of LA in the field of cancer therapy.